U-Pb zircon, geochemical and Sr-Nd-Hf isotopic constraints on age and origin of Jurassic I- and A-type granites from central Guangdong, SE China: A major igneous event in response to foundering of a subducted flat-slab? - Li, X.; Li, Zheng-Xiang; Li, W.; Liu, Y.; Yuan, C.; Wei, G.; Qi, C. (Elsevier Science BV, 2007)
The Mesozoic geology of SE China is characterized by widespread Jurassic to Cretaceous igneous rocks consisting predominantly of granites and rhyolites and subordinate mafic lithologies. However, the tectonic regime responsible for the inland Jurassic granites remains controversial. We report here U–Pb zircon ages, geochemical and Sr–Nd–Hf isotopic data for the Nankunshan alkaline granite and the Fogang granitic batholith in central Guangdong. Mineralogical and geochemical features suggest that the Fogang and Nankunshan rocks are I- and aluminous A-type granites, respectively. SHRIMP U–Pb zircon analyses yield consistent ages ranging from 159±3 Ma to 165±2 Ma for four samples from the Fogang Batholith, and an age of 158±5 Ma for the Nankunshan Granite. The Fogang granites, having ISr=0.7098–0.7136, eNd(T)=-4.3 to -12.2 and eHf(T)=-11.5 to -3.1 for the magmatic zircons, were derived from Paleoproterozoic mafic-intermediate igneous protolith with minor addition of mantle-derived magmas. The Nankunshan rocks have relatively lower ISr˜0.706–0.708, higher eNd(T)=0.3 to -2.4 and eHf(T)= -5.7 to 1.1 for the magmatic zircons, and some OIB-like trace element ratios. They were likely generated through extensive fractional crystallization of mantle-derived alkaline parental magma associated with crustal assimilation. These ~160 Ma I- and A-type granites in central Guangdong were emplaced coeval with the widespread 165–155 Ma I- and A-type granites and syenites following the initiation of intraplate basaltic and/or bimodal igneous magmatism at 180–170 Ma in the adjacent regions. We interpret these Jurassic igneous rocks as anorogenic magmatism formed during a major igneous event in response to foundering of an early Mesozoic subducted flat-slab beneath SE China continent.